2000
DOI: 10.1002/hep.510310325
|View full text |Cite
|
Sign up to set email alerts
|

Iron reduction before and during interferon therapy of chronic hepatitis C: Results of a multicenter, randomized, controlled trial

Abstract: Patients with chronic hepatitis C and low serum and hepatic iron stores may have an improved response to interferon (IFN). We tested whether iron reduction before and during IFN therapy would lead to an improved sustained biochemical and virological response compared with IFN alone. Eighty-two previously untreated patients with chronic hepatitis C were randomized to either: group A IFN-␣2b 3 MU 3 times per week for 6 months, or group B iron reduction before and during IFN-␣2b 3 MU 3 times per week for 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(106 citation statements)
references
References 37 publications
1
98
1
6
Order By: Relevance
“…Results from recent, similarly designed trials of iron reduction with interferon in treatment naive patients suggested that pretreatment iron reduction may improve interferon responsiveness. 22,23 Our study had a relatively high drop-out rate in both study arms. This was perhaps because those patients randomized to phlebotomy alone thought they were receiving a lesser treatment and overall patients may have been discouraged by the fact that serum HCV-RNA levels rarely became negative during treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Results from recent, similarly designed trials of iron reduction with interferon in treatment naive patients suggested that pretreatment iron reduction may improve interferon responsiveness. 22,23 Our study had a relatively high drop-out rate in both study arms. This was perhaps because those patients randomized to phlebotomy alone thought they were receiving a lesser treatment and overall patients may have been discouraged by the fact that serum HCV-RNA levels rarely became negative during treatment.…”
Section: Discussionmentioning
confidence: 73%
“…[3][4][5] In clinical studies, about 30-40% of chronic HCV patients possess elevated serum iron, ferritin and transferrin saturation. 6 A correlation between increased cellular and systemic iron levels and HCV patients with poor prognosis and severe deterioration in liver metabolic processes has been previously reported. 6 However, it remains unclear whether there is any correlation between HCV replication and increased intrahepatic or serum iron in chronic HCV patients.…”
Section: Introductionmentioning
confidence: 87%
“…Smith et al reported that the progression of fibrosis is faster in patients with chronic hepatitis C with congenital hemochromatosis than in those with normal iron levels (7). Fontana et al reported that combination therapy with IFN and phlebotomy may be more effective than IFN monotherapy in patients with chronic hepatitis C (8). We reported the hemosiderin deposition may be a predictive parameter for the efficacy of IFN therapy (9).…”
Section: Introductionmentioning
confidence: 59%